IMPLEMENTATION OF BLOCKCHAIN TECHNOLOGY IN THE ASSESSMENT OF PANCASILA EDUCATION: ENHANCING TRANSPARENCY AND ACCOUNTABILITY IN THE EVALUATION SYSTEM. - Abdusshomad, Alwazir (Institut Pendidikan Indonesia, 2025)
Pancasila education plays a crucial role in shaping character and instilling national values in students. However, in practice, the assessment system still faces various challenges, particularly in terms of transparency and accountability. This study aims to explore the utilization of blockchain technology as a solution to enhance clarity and accountability in the assessment of Pancasila education. This research employs a library research method by analyzing various references related to the implementation of blockchain technology in education. The findings indicate that blockchain can be utilized as a secure, transparent, and tamper-resistant data recording system. This technology contributes to creating a more objective and reliable evaluation process, thereby increasing trust in the education system. Thus, the implementation of blockchain has the potential to strengthen character development based on Pancasila values through a fairer and more effective assessment system